2015
DOI: 10.16916/aded.43181
|View full text |Cite
|
Sign up to set email alerts
|

Türkçe Öğretiminde Drama

Abstract: ÖzTürkçe dersinde drama yöntem ve tekniklerinin kullanıldığı etkinlikler ile: çocuklar metinleri daha iyi anlayabilme; aldıkları çeşitli roller sayesinde empati kurabilme; sağlıklı ve etkili iletişim kurabilme; duygu, düşünce ve hayallerini yaratıcı bir şekilde sözlü ve yazılı olarak dile getirebilme; eleştirel ve empatik dinleyebilme; dinlediklerini ve okuduklarını analiz ederek özetleyebilme; izlediklerini eleştirebilme, olaylar arasında ilişki kurabilme, sesini ve beden dilini etkili kullanabilme gibi yeter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
3
0
5
Order By: Relevance
“…The reasons for the use of creative drama as a method in education can be listed as follows; being student-centred, based on the process, making the student active and providing the student with the opportunity to express himself/herself (Özbey & Sarıkaya, 2019). Through student-centred drama activities, many abstract, complex and different subjects can be made concrete in the mind of the student through enactment (Kurudayıoğlu & Özdem, 2015). Given the delineations above, it can be said that creative drama is a method that increases students' interest in and desire for the lesson and helps them develop positive attitudes towards the lesson.…”
Section: Yaratıcı Dramanın Türkçe Dersine Ve Türkçe Dil Becerilerine ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for the use of creative drama as a method in education can be listed as follows; being student-centred, based on the process, making the student active and providing the student with the opportunity to express himself/herself (Özbey & Sarıkaya, 2019). Through student-centred drama activities, many abstract, complex and different subjects can be made concrete in the mind of the student through enactment (Kurudayıoğlu & Özdem, 2015). Given the delineations above, it can be said that creative drama is a method that increases students' interest in and desire for the lesson and helps them develop positive attitudes towards the lesson.…”
Section: Yaratıcı Dramanın Türkçe Dersine Ve Türkçe Dil Becerilerine ...mentioning
confidence: 99%
“…In these studies, it was concluded that creative drama positively affects academic achievement and attitude towards the lesson. Within the context of language teaching, it has been concluded that creative drama is an effective method in developing students' language skills (Aykaç & İlhan, 2014;Galente & Thomson, 2017;Jie, 2021;Susar-Kırmızı, 2015;Öztürk-Pat & Yılmaz, 2021;Terzioğlu-Ünveren, 2018;Türkel & Öz, 2020), vocabulary (Arpağ, 2018;Kır-Cullen, 2021;Koçpınar, 2018;Metinnam & Erdoğan, 2016, Şahin, 2018Şenol, 2011) and in the teaching of grammar (Kodaz, 2007;Özkaya and Altuntaş, 2021;Şimşek et al, 2010;Teke & Gedizli, 2016;Türkel & İnnalı, 2020;Yeşilyurt, 2011) and that it increases students' interest in the lesson (Aytaş & Özcan, 2019;Keşaplı, 2019;Kurudayıoğlu & Özdem, 2015;Özcan, 2020). There are also experimental studies examining the effects of creative drama on students' attitudes towards Turkish lessons and Turkish language skills (Çam-Türkan, 2020;Erden, 2016;Erdoğan, 2013;Erdoğan, Erdoğan & Uzuner, 2018;Ergüder, 2019;Erkan & Aykaç, 2014;İsbir-Abrekoğlu, 2019;Kara, 2010;Kardaş, 2018;Kılıç, 2018;Öz, 2018;Özber, 2019;Susar-Kırmızı, 2008;Tanrıkulu & Yoğurtçu, 2018...…”
Section: Yaratıcı Dramanın Türkçe Dersine Ve Türkçe Dil Becerilerine ...mentioning
confidence: 99%
“…Nitekim öğrenilen bilgilerin kalıcı olması, bilginin günlük gerçek yaşamla ilişkilendirilmesi ile mümkün olmaktadır. Drama bu amaca hizmet eden en etkili yöntemlerden olarak görülmekte ve bütün eğitim kademelerinde bu yönteme yer verilmesi gerektiği birçok araştırmacı tarafından belirtilmektedir (Aykaç ve Çetinkaya, 2013;Çelikkaya, 2014;Kara, 2000Kara, , 2007Kara, , 2008Kara, , 2009Kara, , 2011Kardaş, 2016b;Kırmızı, 2008;Kurudayıoğlu ve Özdem, 2015;Durukan, 2012;Maden, 2010cMaden, ,2010bMaden, , 2010aMaden, , 2011aMaden, , 2011b. Alan uzmanlarının eğitimöğretim çalışmalarında hararetle drama yöntemini önermelerinin önemli gerekçelerden biri, öğrenenlerin çekinmeden, endişe duymadan iletişime geçmelerine katkı sağlamasıdır.…”
Section: Kuram Ve Uygulamada Sosyal Bilimler Dergisiunclassified
“…Literatür incelendiğinde yaratıcı drama ile ilgili çalışmalar eğitimde yaratıcı drama adıyla (San, 1990;Öztürk, 2001;MEB, 2014) yer almakla birlikte sonrasında özelleştirilmiş ve çalışma grubumuzu da içeren Türkçe öğretiminde drama ve drama yönteminin gerekliliği ile Türkçe öğretmenlerinin yaratıcı drama yöntemini kullanımları üzerine çalışmalarla (Kurudayıoğlu ve Özdem, 2015;Maden, 2010;Eyüp ve Kırbaşoğlu Kılıç, 2013) alandaki yerini almıştır. Bu çalışmalar da dramanın önemini vurgulamada çalışmamızın önemi noktasında yol gösterici olmaktadır.…”
Section: Introductionunclassified